Enterococcus faecalis Bacteriophage 156 Is an Effective Biotechnological Tool for Reducing the Presence of Tyramine and Putrescine in an Experimental Cheese Model - del Rio, Beatriz; Sánchez-Llana, Esther; Redruello, Begoña; Magadan, Alfonso H.; Fernández, María; Martin, Maria Cruz; Ladero, Victor; Alvarez, Miguel A. (Frontiers in Microbiology, 2019)
Biogenic amines (BA)-nitrogenous compounds of low molecular weight- are the result of metabolism of certain amino acids. They are biologically present in all living organisms and play essential physiological roles. However, their accumulation in foodstuffs due to the metabolic activity of certain microorganisms represents a toxicological risk. Containing such microorganisms, and with an abundance of precursor substrate amino acids, fermented foods in general, and cheeses in particular, provide an ideal matrix for the accumulation of these toxic compounds. Unfortunately, the main microorganisms responsible for BA accumulation are members of the lactic acid bacteria (LAB) group, which are also essential for the development of the organoleptic characteristics of the final product. The methods used to reduce the BA content of cheese, such as milk pasteurisation, commonly fail to do so, and affect desirable non-BA-producing lactic acid bacteria (LAB) as well. Bacteriophages have been proposed as biotechnological tools for diminishing the presence of undesirable microorganisms in dairy products. Given their specificity, they could be used to target the population of BA-producing bacteria. In this work, we aimed to explore the use of Enterococcus faecalis infecting phages as a tool to reduce the content of BA in dairy products. For this, we proceeded to the isolation and characterisation of E. faecalis bacteriophage 156, a member of the family Myoviridae. Its genome was sequenced and compared with that of E. faecalis family Myoviridae phages available in public databases. Its capacity to decrease the accumulation of the BA tyramine and putrescine in an experimental laboratory-scale cheese model was proven.